2018
DOI: 10.31234/osf.io/b25tf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced habit-driven errors in Parkinson’s Disease

Abstract: Parkinson’s Disease can be understand as a disorder of motor habits. A prediction of this theory is that early stage Parkinson’s patients will display fewer errors caused by interference from previously over-learned behaviours. We test this prediction in the domain of skilled typing, where actions are easy to record and errors easy to identify. We describe a method for categorising errors as simple motor errors or habit-driven errors. We test Spanish and English participants with and without Parkinson’s, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Learning on the accelerating rotarod has also been used to model acquired repetitive behaviors in mouse models of autism, which have coincident changes in striatal circuitry (Rothwell et al, ). In human patients with Parkinson's disease, in whom nigrostriatal dopamine signaling is impaired, there are deficits in new motor skill acquisition (Kawashima, Ueki, Kato, Ito, & Matsukawa, ) as well as in habit (Bannard et al, ; Knowlton, Mangels, & Squire, ; Witt, Nuhsman, & Deuschl, ).…”
Section: Tasks To Probe Habits In Animal Modelsmentioning
confidence: 99%
“…Learning on the accelerating rotarod has also been used to model acquired repetitive behaviors in mouse models of autism, which have coincident changes in striatal circuitry (Rothwell et al, ). In human patients with Parkinson's disease, in whom nigrostriatal dopamine signaling is impaired, there are deficits in new motor skill acquisition (Kawashima, Ueki, Kato, Ito, & Matsukawa, ) as well as in habit (Bannard et al, ; Knowlton, Mangels, & Squire, ; Witt, Nuhsman, & Deuschl, ).…”
Section: Tasks To Probe Habits In Animal Modelsmentioning
confidence: 99%
“…36 In humans, dopamine-depleted Parkinson's patients exhibit deficits in habitual control. 6,37,38 However, although dopamine is indubitably involved in habit formation, its regional specificity and its involvement in the widely assumed regional shift of behavioral control during the transition from goal-directed to habitual behavior is understudied. Conclusions were advanced on the grounds of anatomical studies and sparse functional evidence: one study tracked regionally shifting striatal dopamine signaling across development of a presumed habit reinforced by cocaine, 31 whereas another study reported no such shift using a natural reinforcer.…”
Section: Introductionmentioning
confidence: 99%
“…This selective loss seems to alter automatic moves such as arm swinging during walking or facial expressions in social interactions. More recently habitual components of typing (Bannard et al, 2019) and associative learning (Mi et al, 2021) seem to be reduced in Parkinson’s disease. In contrast, Huntington disease induces neural atrophy specifically in the head of the caudate (Vonsattel and DiFiglia, 1998) preventing the initial associations needed to integrate the repetition of stimulus-response associations into habits (Holl et al, 2012; Willingham and Koroshetz, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between these newly acquired stimulus-response associations and those acquired naturally over a lifetime when conducting everyday activities, is uncertain. It is equally important to understand how these important functional systems might malfunction, as reflected in brain disorders such as Parkinson’s disease (Bannard et al, 2019; Redgrave et al, 2010b), obsessive-compulsive disorder (Gillan, 2021), and drug addictions (Sjoerds et al, 2013), where dysfunctional patterns of habits are evident. Despite the obvious importance of habitual control, formal investigations of stimulus-response associations established in everyday-life are notably absent.…”
Section: Introductionmentioning
confidence: 99%